Odpowiedzi

2010-03-23T19:15:18+01:00
5*(x+3)=-25
5x + 15= -25
5x= -25 -15
5x= -40 : 5
x = 8

7*(y+1)=42
7y+ 7 = 42
7y = 42 - 7
7y = 35 : 7
y = 5


4*(z-4)=96
4z-16=96
4z=96+16
4z = 112: 4
z = 28


6*(t-2)=-54
6t - 12 = - 54
6t = -54 -12
6t = -68 ; 6
t = 11,3



nie rozumiem dalszego zapisu
2010-03-23T19:26:43+01:00
5*(x+3)=-25
5x+15=-25
5x=-25-15
5x=-40 II /5
x=8

7*(y+1)=42
7y+7=42
7y=42-7
7y=35 II /7
y=5

4*(z-4)=96
4z-16=96
4z=96+16
4z=112 II/4
z=28

6*(t-2)=-54
6t-12=-54
6t=-54+12
6t=-42 II/6
t=7

-*(a+4)=6
-a-4=6
-a=6+4
-a=10 II/-1
a=-10

-*(b+5)=-1
-b-5=-1
-b=-1+5
-b=4 II/-1
b=-4

tyle z tego rozumiem